2021
DOI: 10.3126/zooj.v5i0.34919
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment 0f Water Quality in the Bagmati River Basin, Nepal

Abstract: Kathmandu, the capital city of Nepal is one of the most populated destinations of the country. The water pollution remains a challenging issue for the sustainable development in the valley despite several pollution control devices, awareness-raising and policy measures. During monsoon period 2018, surface water samples were collected from 10 sites of the Bagmati River and its tributaries within the valley to evaluate the water quality. The different physico-chemical parameters were determined to assess polluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…The results indicated that variations in the hydrochemical parameters in the BRB were mainly controlled by the extent of anthropic activities which were also consistent with the previous studies ( Paudyal et al, 2016 ; Pal et al, 2019 ). It has clearly revealed that the relatively low concentrations of hydrochemical parameters during the post lockdown ( Table 1 ) indicate the imprints of lockdown in the core urban area.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…The results indicated that variations in the hydrochemical parameters in the BRB were mainly controlled by the extent of anthropic activities which were also consistent with the previous studies ( Paudyal et al, 2016 ; Pal et al, 2019 ). It has clearly revealed that the relatively low concentrations of hydrochemical parameters during the post lockdown ( Table 1 ) indicate the imprints of lockdown in the core urban area.…”
Section: Resultssupporting
confidence: 91%
“…Comparing to the global average i.e., 120 mg/L ( Gaillardet et al, 1999 ), the TDS values were 4.69 and 1.89 times higher during pre-lockdown and post-lockdown periods, respectively ( Table 1 ). Generally, the TDS values were found to be < 120 mg/L in most of the freshwater rivers, but the higher values observed even in post lockdown could be due to municipal wastes and agricultural runoff in the BRB ( Pal et al, 2019 ; Paudyal et al, 2016 ). Also, the EC dropped from 956 μS/cm to 431 μS/cm, indicating substantially less dissolved materials in the river water during post-lockdown.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The contamination of freshwater bodies can result in low drinking and irrigation water quality and cause potential human and ecological health problems. In general, the fluctuation in the parameters, including ionic constituents in water beyond the permissible level due to various natural and anthropogenic processes (Pal et al 2019;Pant et al 2021a) Although Nepal is rich in freshwater resources, the Ramsar sites and other freshwater lakes are under high pressure due to various anthropogenic activities and global climate change (Zhang et al 2019). Overdependence on the water to meet the ever-increasing demands of domestic, agricultural, industrial, and haphazard developmental activities has resulted in the overexploitation of water resources and deteriorated lake water quality in Nepal (Rupakheti et al 2017).…”
Section: Introductionmentioning
confidence: 99%